TEACHING RUSSIAN AS A FOREIGN LANGUAGE TO STUDENTS OF NATURAL SCIENCES - Fatima Abdugafurovna Abdusalamova (International Journal of Literature and Language Studies, 2026)
The article examines the specific features of teaching Russian as a foreign language (RFL) to students majoring in natural sciences. The main objectives and outcomes of the study are identified, and methods and approaches that contribute to effective learning are proposed. Particular attention is paid to the integration of scientific terminology and the practical application of language skills in professional activities.